2022
DOI: 10.1002/mp.15680
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect of X‐ray abdominal FLASH irradiation: Adaptation to oxidative damage and inflammatory response may be benefiting factors

Abstract: Background Ultrahigh dose‐rate irradiation (FLASH‐IR) was reported to be efficient in tumor control while reducing normal tissue radiotoxicity. However, the mechanism of such phenomenon is still unclear. Besides, the FLASH experiments using high energy X‐ray, the most common modality in clinical radiotherapy, are rarely reported. This study aims to investigate the radiobiological response using 6 MV X‐ray FLASH‐IR or conventional dose‐rate IR (CONV‐IR). Methods The superconducting linac of Chengdu THz Free Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…FLASH-RT was performed using the Chengdu THz Free Electron Laser (CTFEL) facility that produces 6 MV bremsstrahlung X-rays [4] , [5] . A 5-cm-thick lead shield with a 2-cm (craniocaudal) × 4-cm (lateral) window was used for FLASH-RT, and the mice received RT at a source surface distance (SSD) of 13.5 cm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FLASH-RT was performed using the Chengdu THz Free Electron Laser (CTFEL) facility that produces 6 MV bremsstrahlung X-rays [4] , [5] . A 5-cm-thick lead shield with a 2-cm (craniocaudal) × 4-cm (lateral) window was used for FLASH-RT, and the mice received RT at a source surface distance (SSD) of 13.5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a series of preclinical studies have shown that FLASH-RT reduced the expression levels of transforming growth factor-beta, a maker of tissue damage and a key switch for fibrosis initiation [20] , [21] . A previous study found that FLASH-irradiated BALB/c nude mice had significantly fewer inflammatory blood cells and diminished pro-inflammatory cytokines 4 weeks post-irradiation (PI), which might be beneficial factors in reducing radiotoxicity after FLASH-RT [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that FLASH-RT had less expression of pro-inflammatory factor gene (EGR1) and lower up-regulation of inflammatory factor (TGF-b1, NF-KB) than COVN-RT. Zhu et al (26) reported the changes of immune and inflammatory responses after FLASH-RT(>150Gy/s, 10Gy and 15Gy) irradiation on the intestine of mice(BALB/c). X-ray was used in Zhu's study.…”
Section: Effect Of Flash-rt On Immune Functionmentioning
confidence: 99%
“…An average dose rate above 40 Gy/s has long been the main characteristic that defines FLASH RT. However, it seems that a higher dose rate is often needed to observe a reduction in normal tissue toxicity, depending on the target tissue (brain [ 24 , 32 , 34 ] and abdomen [ 25 , 42 , 44 ] vs. thorax [ 17 , 36 , 37 , 38 ]) and the used in vivo model (zebrafish embryos [ 22 ] vs. mice [ 31 , 46 ]). In addition to the dose rate, a dose threshold also strongly impacts the FLASH effect.…”
Section: Beam Parameters Necessary To Trigger the Flash Effectmentioning
confidence: 99%